Prevalence and levels of permethrin resistance in Pediculus humanus capitis de Geer (Anoplura: Pediculidae) from Buenos Aires, Argentina - Vassena, Claudia Viviana (2003)
Permethrin has been used extensively for control of Pediculus humanus capitis De Geer (Anoplura: Pediculidae) in Argentina since 1990, resulting in the development of resistance to this and other pyrethroids. This resistance was first detected in some field populations in 1997. A survey for resistance in Buenos Aires in 2001 revealed significant resistance levels in lice on children at 24 of 26 (92.3%) schools. When compared with a previously unexposed reference population, resistance ratios (RRs) obtained by exposing the insects to filter papers impregnated with permethrin ranged from 2 to 60 in 10 (39%) of the schools. RRs in the remaining 14 (61%) populations were too great to not be measured with the filter paper method (RR > 88.7). As an alternative, we used topical applications of 0.1 μl of acetone solution of permethrin on the dorsal abdomen of adults and third instars. This topical method, which has not been previously reported for head lice, was capable of quantifying higher levels of resistance. Highly resistant populations had RRs from 162.5 to 655.2. When applied to populations with low and intermediate levels of resistance, results from the filter paper and topical application methods were highly correlated, and RRs from topical application were higher than those from the filter paper method. Results from the combination of the two methods indicated that head lice among Buenos Aries school children are highly resistant to permethrin, and the resistance is widespread.